Untimely epic Apollonius Rhodius' Argonautica - Phillips, Tom 1984- (Oxford University Press, 2020)
Apollonius Rhodius' Argonautica is a voyage across time as well as space. The Argonauts encounter monsters, nymphs, shepherds, and kings who represent earlier stages of the cosmos or human society; they are given glimpses into the future, and themselves effect changes in the world through which they travel. Readers undergo a still more complex form of temporal transport, enabled not just to imagine themselves into the deep past, but to examine the layers of poetic and intellectual history from which Apollonius crafts his poem. Taking its lead from ancient critical preoccupations with poetry's ethical significance, this book argues that the Argonautica produces an understanding of time and temporal experience which ramifies variously in readers' lives
Also issued in print: 2020. - Includes bibliographical references and index
Keywords: Apollonius / Rhodius / Argonautica; Apollonius -- Rhodius -- v295-v215 -- Argonautica; Epic poetry, Greek / History and criticism; Argonauts (Greek mythology) in literature